Analyzing Errors: An Examination of Simple Present Tense Usage in Descriptive Text - Zul Astri; Karmila Mokoginta; Fhadli Noer; Multazam Abubakar; Nurul Hidjrah Hairuddin (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2023)
This study investigates the common errors made by students when using the simple present tense in writing descriptive texts. The aim of the study is to identify the specific types of errors that occur and to explore the factors contributing to these mistakes. The research adopts a descriptive qualitative method to gather data, employing a written test as the data collection tool. To categorize the errors, a surface strategy taxonomy is utilized, which includes four categories: omission, addition, misformation, and misorder. By analyzing the collected data, a total of 214 errors were identified, with 95 instances of omission errors, 22 addition errors, 75 formation errors, and 22 ordering errors. The findings highlight that the most prevalent type of error made by students is omission, while misformation, misorder, and addition errors are relatively less frequent. In addition to error analysis, the study explores the reasons underlying these errors, particularly focusing on interlingual and intralingual transfer. Interlingual transfer refers to the influence of a student's first language on their second language usage, while intralingual transfer refers to the influence of existing knowledge and patterns within the second language itself. These factors contribute to the occurrence of errors in the simple present tense usage within descriptive texts.